Impact of social stigma on the process of obtaining informed consent for genetic research on podoconiosis: a qualitative study - Tekola, F; Bull, S; Farsides, B; Newport, M; Adeyemo, A; Rotimi, C; Davey, G (BioMed Central, 2009)
Background: The consent process for a genetic study is challenging when the research is conducted in a group stigmatized because of beliefs that the disease is familial. Podoconiosis, also known as 'mossy foot', is an example of such a disease. It is a condition resulting in swelling of the lower legs among people exposed to red clay soil. It is a very stigmatizing problem in endemic areas of Ethiopia because of the widely held opinion that the disease runs in families and is untreatable. The aim of this study was to explore the impact of social stigma on the process of obtaining consent for a study on the genetics of podoconiosis in Southern Ethiopia. Methods: We adapted a rapid assessment tool validated in The Gambia. The methodology was qualitative involving focus-group discussions (n = 4) and in-depth interviews (n = 25) with community members, fieldworkers, researchers and staff of the Mossy Foot Treatment and Prevention Association (MFTPA) working on prevention and treatment of podoconiosis. Results: We found that patients were afraid of participation in a genetic study for fear the study might aggravate stigmatization by publicizing the familial nature of the disease. The MFTPA was also concerned that discussion about the familial nature of podoconiosis would disappoint patients and would threaten the trust they have in the organization. In addition, participants of the rapid assessment stressed that the genetic study should be approved at family level before prospective participants are approached for consent. Based on this feedback, we developed and implemented a consent process involving community consensus and education of fieldworkers, community members and health workers. In addition, we utilized the experience and established trust of the MFTPA to diminish the perceived risk. Conclusion: The study showed that the consent process developed based on issues highlighted in the rapid assessment facilitated recruitment of participants and increased their confidence that the genetic research would not fuel stigma. Therefore, investigators must seek to assess and address risks of research from prospective participants' perspectives. This involves understanding the issues in the society, the culture, community dialogues and developing a consent process that takes all these into consideration.